1978
DOI: 10.1021/j100497a025
|View full text |Cite
|
Sign up to set email alerts
|

An electron spin resonance study of the photolysis of trapped radicals in .gamma.-irradiated carboxylic esters at 77-87 K

Abstract: Sir: Although several ESR studies have shown that the photolysis of trapped radicals in -irradiated carboxylic esters, RC(0)0R', at (or near) 77 K leads to the formation of alkyl radicals,1™3 the literature is often confusing and even contradictory on the question of whether R• or R'• is the product radical. Thus, the UV photobleaching of -irradiated ethyl acetate and methyl pivalate is reported to give the methyl radical in each case despite the different locations of the methyl group (R and R', respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This type of radical has been previously observed in long-chain n-alkanes14 as well as palmitic acid. 13 No other radical can yield the same total width. This radical probably results from ionization followed by deprotonation from the alkyl side chain.…”
Section: Hc(010ch2ch3 -Hcof + Ch2ch3mentioning
confidence: 99%
See 1 more Smart Citation
“…This type of radical has been previously observed in long-chain n-alkanes14 as well as palmitic acid. 13 No other radical can yield the same total width. This radical probably results from ionization followed by deprotonation from the alkyl side chain.…”
Section: Hc(010ch2ch3 -Hcof + Ch2ch3mentioning
confidence: 99%
“…•R' + RCH2C02R' -R'H + RCHC02R' (13) Methyl and ethyl formate anions lead to hydrogen abstraction from the formate group (reactions 2 and 4). In addition, results for methyl formate and perhaps other esters suggest that direct hydrogen abstraction by the ester anion may also be important to ester anion decay (reaction 14).…”
Section: Hc(010ch2ch3 -Hcof + Ch2ch3mentioning
confidence: 99%
“…Huddson and Williams studied the radiolysis of carboxylic esters and found that RCOOtHCn-1 H 2 n-1 radicals are photodecomposed into acyl-type radicals by UV irradiation, 13 as…”
mentioning
confidence: 99%
“…Experiments have shown that photolysis of these radical anions produces ethyl and methyl radicals, respectively, the products expected from 8-scission reactions. 20 The operation of the 8-scission reaction in these ester systems therefore suggests the likely occurrence of ß scission in the carbonate systems.…”
Section: ^C-ocha H5ccrmentioning
confidence: 94%